ANALYSIS OF SENSITIZATION FEATURES TO WEED POLLEN AND EFFICACY OF ALLERGEN IMMUNOTHERAPY IN PATIENTS OF THE CENTRAL AND WESTERN REGIONS IN UKRAINE - Zubchenko, S.O.; Sharikadze, O. (World of Medicine and Biology, 2018)
Incidence of sensitization is changing geographically based on multiple environmental factors. About 1.5 thousand different types of weeds are common in Ukraine. Climatic and geographical conditions such as air temperature, humidity and plant diversity in the region is of great importance in the prevalence of allergic diseases. Allergy to weeds is a global problem due to development of respiratory allergy – seasonal allergic rhino-conjunctivitis (hay fever) with/without bronchial asthma in patients living in Ukraine. Allergen immunotherapy is a disease-modifying treatment for patients with seasonal hay fever with/without bronchial asthma. However, in Ukraine there are little data on the efficacy of sublingual form of allergen immunotherapy. The use of standardized sublingual immunotherapy is efficient in treating patients with seasonal hay fever with/without bronchial asthma.
Keywords: Ambrosia; Artemisia; molecular allergodiagnosis; VAS; SLIT efficacy